Critical Analysis of Midwives’ Impact on Maternal and Neonatal Health in Saudi Arabia - Al-Shahrani, Hoda Nasser Fayez; Alshahrani, Hanan Dafer; Al-Masaad, Neamah Mesfer Masaad; Almusaad, Thuraya Mesfer Musaad; Al-Musaad, Hamdah Mesfer Musaad; Dakam, Faris Ahmed Mohammed; Almihithal, Wijdan Misfer Horgan; Alsaad, Ghadeer Mubarak Saed; Al Saad, Hamad Mohammed Hamad; Fawaz, Amira Hussein Nasser (Journal of Ecohumanism, 2024)
Specifically, this paper discusses how midwives influence maternal and neonatal health care in Saudi Arabia. This paper contributes to filling this gap by providing an analysis of the role of midwives despite improvements in the health care system’s stock and decreasing maternal and neonatal mortality ratios. The research concerns midwives’ role in shaping the nature of care, maternal and neonatal health, and maternity care systems. The information was obtained both from structured and unstructured documents, interviews with healthcare professionals, surveys, and statistical health reports. Findings reveal that midwives contribute a lot to providing ANC, skilled birth attendance, and PNC but are constrained by factors including inadequate training, poor deployment, and practices that are culturally irrational. Based on the paper’s findings, recommendations are made to enhance and expand midwifery services in Saudi Arabia.